Countering the pedagogic hegemony of neo-liberalism in the workplace: a Freirean analysis of the contribution of union-led learning to enhanced worker participation in the UK. Issue 1 (1st September 2020) - Bennett, Tony
Abstract : Purpose: The purpose of this paper is to critically assess the degree to which current union learning strategy and practice in the UK can become a catalyst for greater activism and participation by their members in the workplace and beyond. To this end, the paper seeks to draw on the rich heritage of pedagogic theory and practice in adult education writing to bring a fresh perspective to a key aspect of industrial relations. Design/methodology/approach: Through a meta-analysis of the current literature on the role of union learning representatives, learning centres and the context of that learning, the paper seeks to enhance understanding of how such initiatives in addition to upskilling workers lead to members' greater enlightenment with respect to the asymmetric power relations within the workplace and society. Using a conceptual model devised by the author from Freirean theory, this potentially increased awareness of their position in the organisation and society leading to greater levels of subsequent activism and participation by these learners is then critically assessed. Findings: Utilising the radical perspective of Paulo Freire, the article critically analyses the key elements of current union learning strategies in the UK. The paper concludes that union pedagogy strategy not just often raises members' awareness, as Freire would advocate, of their "subordinate" position in society, but potentially also genuinely equips them with the skills, knowledge and understanding to challenge that position through subsequent union activism and, therefore, greater participation in decision-making in the workplace. Union-facilitated learning, it is argued, can also develop the skills and knowledge necessary to increase members' job security. Originality/value: To the author's knowledge, this is the first time that a Freirean analysis has been applied to this key element of contemporary trade union strategy and practice. In particular, the study seeks to also go beyond most studies of union pedagogic approaches and focus on the learner's journey and how this may imbue a propensity to become more active in the union and, therefore, the workplace.